Virtual and Augmented Reality versus Traditional Methods for Teaching Physiotherapy: A Systematic Review - David Lucena-Anton; Juan Carlos Fernandez-Lopez; Ana I. Pacheco-Serrano; Cristina Garcia-Munoz; Jose A. Moral-Munoz (MDPI AG, 2022)
The use of virtual worlds in health-related education is increasingly popular, but an overview of their use in physiotherapy education is still needed. The aim of this review was to analyse the use of virtual and augmented reality (VR/AR) compared to traditional methods for teaching physiotherapy. A systematic review was performed up to October 2022 in PubMed, Web of Science, Scopus, CINAHL, and PsycInfo. The quality appraisal and risk of bias were assessed by the Joana Briggs Institute checklist and the Cochrane Collaboration's RoB Tool 2.0, respectively. A total of seven randomised and non-randomised controlled studies were included, involving 737 students. VR/AR-based teaching approaches included simulation and virtual worlds, and were conducted through immersive head-mounted displays, AR-based applications, and 3D visualisations. Three studies were focused on teaching anatomy content, two on clinical decision making skills, and the rest were focused on pathology, physiotherapy tasks or exercise performance, and movement analysis of lower limbs. Inconclusive results were found in terms of learning satisfaction and academic performance, showing VR/AR-based teaching models to be equally effective as traditional methods for teaching physiotherapy. We encourage researchers and teachers to include games in their VR/AR-based teaching approaches to enhance interaction and active learning in physiotherapy education.